Clinical and therapeutic implications of BRAF mutation heterogeneity in metastatic melanoma. (7th March 2017) - Mesbah Ardakani, Nima; Leslie, Connull; Grieu‐Iacopetta, Fabienne; Lam, Wei‐Sen; Budgeon, Charley; Millward, Michael; Amanuel, Benhur
Summary: Heterogeneity of BRAF mutation in melanoma has been a controversial subject. Quantitative data on BRAF allele frequency (AF) are sparse, and the potential relationship with response to BRAF inhibitors ( BRAFi ) in patients with metastatic melanoma is unknown. We quantitatively measured BRAF AF in a cohort of treatment naïve metastatic melanoma samples by pyrosequencing and correlated with survival data in patients treated with BRAFi as part of their clinical care. Fifty‐two samples from 50 patients were analysed. BRAF V600E mutations were detected in 71.1% of samples followed by V600K (25%) and V600R (3.9%). There was a wide range of AF from 3.9% to 80.3% (median 41.3%). In 33 patients treated with BRAFi, there was no difference in overall or progression‐free survival when the patients were categorized into high or low AF groups. There was no correlation between AF and degree of response, and no difference in survival based on genotype.